Analisis Kebutuhan Air Peternakan Daerah Aliran Sungai Binjai Pulau Natuna - Permata Amanda De Novin; Manyuk Fauzi; Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
Binjai watershed is one of nine watersheds on Natuna Island which has the largest area of 643.62 km2. Along with regional development and population growth, the need for livestock also continues to increase, because it is intended to meet people's meat consumption. In the field of animal husbandry, water is very necessary for the development of livestock. Water demands of livestock will continue to increase in accordance with the growth of livestock. This study uses the library research or study literature, taken from secondary data by the relevant government. The result of this study are that in 2010 livestock water demands was 30.15 m3/day, in 2020 livestock water demands was 44.96 m3/day, while the projection in 2040 livestock water demands is 82.60 m3/day. It can be concluded that there is an increase in livestock water demands for each year.Keywords : binjai watershes, livestock water demans, projection.